Suitability Analysis on Swimming Recreation in Bintalahe Beach - Farida H Adam; Femy Sahami; Citra Panigoro (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to assess the suitability of Bintalahe Beach Tour as a place to Swim in Kabila Bone District, Bone Bolango Regency, Gorontalo Province. The location of the study was divided into five stations. Parameters measured include Water depth, Bottom substrate, Current velocity, Wave height, Coastal type, Coastal width, Water transparency, Hazardous biota, Freshwater availability, Tidal, Beach Tilt. The data analysis was performed based on the calculation of Beach Tourist Suitability Index. The result of this research indicate that the value of Coastal Equality Index of Bintalahe Coast is about 64,166 - 71,66% which means it is included in the category of Conditional Suit. Keywords: Swimming; recreation; beach; suitability